Biografsko-narativni metodološki pristop za poučevanje in razumevanje vsebin slovenskega izseljenstva - Ilc Klun, Mojca (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2017)
The article presents the biographic-narrative methodological approach (BINM), which can be used for teaching, understanding and evaluating the topic of Slovenian emigration. We think that through BINM approach young people can more effectively learn about the topic of Slovenian emigration and it can motivate them for their own research.
Keywords: demografija; demography; education; human migration; izobraževanje; metodika pouka; migracije; slovenski izseljenci